Становлення спортивного права як комплексної галузі в правовій системі України - Чередник, Р. В.; Чередник, Р. В..; Cherednik, R. (My University, 2011)
This article is the attempt of determination of complexity of sport law and determining his location in the system of the Ukrainian legislation. Today in scientiﬁ c works in detail worked only separate, mainly applied, aspects of func- tioning of sports law. The author of the article use conception of complex industry of legislation which is developed modern legal science, which applicability is grounded for description of sports law. The aim of the article is a ground of in- dependence of sport law as an element of the system of legislation of Ukraine.
Чередник Р. В. Становлення спортивного права як комплексної галузі в правовій системі України / Р. В. Чередник // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 201. – Вип. 42. – С. 272-280.
Keywords: Спортивне право; правова система України; функціонування спортивного права; становлення спортивного права; правовая система Украины; функционирование спортивного права; становление спортивного права; formation of sports law; operation of sports law; the legal system of Ukraine; спортивное право; sports law